The Effectiveness of Group Counseling using Mandala Expressive Art Therapy Technique to Reduce Academic Stress of Junior High School Students - Yurianto, Ardini Farzana; Nursalim, Mochamad; Setiawati , Denok; Ghozali, Muhamad Afifuddin (IKIP Siliwangi, 2025)
The state of students who are bored and stressed is included in an unstable psychological condition. This psychological condition can affect the success of the learning process. One of the techniques that can be used by guidance and counseling teachers related to academic stress problems is the mandala expressive art therapy technique. This study aims to determine the effectiveness of mandala expressive art therapy techniques in group counseling to reduce the academic stress of junior high school students. This study used a one-group pre-test and post-test design, adapted from the Educational Stress Scale for Adolescents (ESSA) scale. The subjects of this study were six second-grade students of SMP Negeri 26 Surabaya. The data analysis technique used was the Wilcoxon Signed Rank Test. Based on the results of the output test statistics, it can be seen that the Asymp.Sig (2-tailed) value is 0.027, which is smaller than 0.05. So Ha is accepted, and Ho is rejected, which means that the mandala expressive art therapy technique in group counseling effectively reduces the academic stress of junior high school students. This research contributes as a reference for guidance and counseling teachers in designing art-based intervention programs to help students who experience academic stress.